DELAYED DIAGNOSIS OF PRIMARY ALDOSTEONISM IN A PATIENT WITH AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE - L, Xe Hui; YA, Nor Shaffinaz (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Hypertension is a common manifestation for both autosomal dominant ppolycystic kidney disease (ADPKD) and primary aldosteronism (PA). The occurrence of PA in ADPKD patients is extremely rare. The presence of multiple renal cysts makes identification of adrenal adenomas very challenging. Approximately 5 to 10 percent of adults with hypertension have a secondary cause. Hypertension is a common early finding in ADPKD, occurring in 50 to 70 percent of cases before any significant reduction in glomerular filtration rate. Cross-sectional and prospective studies report PA in >5% and possibly >10% of hypertensive patients, both in general and in specialty settings. PA is a condition well worth detecting because it is associated with excessive morbidity. We report an interesting case of a man with hypertension secondary to ADPKD being diagnosed with PA 9 years later. CONCLUSION Patients with PA have higher cardiovascular morbidity and mortality than age- and sex-matched patients with essential hypertension and the same degree of BP elevation. Diagnosing and treating patients with PA ameliorate the impact of this condition on important patient outcomes. Only a minority of patients with PA (9 to 37%) present with hypokalaemia, with hypokalaemia probably present in only the more severe cases. PA should be suspected when hypokalaemia occurs in a patient with hypertension. The echogenicity of the adrenal glands is similar to that of the retroperitoneal fat. It is even more difficult to visualize the adrenal glands on the ultrasound of a patient with polycystic kidneys. Hence, the methods of choice in the assessment of adrenal pathologies are computed tomography and magnetic resonance imaging.